ANALISIS FONOLOGI BAHASA ARAB: Tinjauan Linguistik Modern - Moch. Mu'izzuddin (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2002)
The abstract of this article as shown in the paper.